Preliminary studies on biology of Parabemisia myricae (Kuwana) and its entomophagous in Sicily and Calabria (Bollettino di zoologia agraria e bachicoltura, 2024)
The results are given in the present paper of preliminary biologica! observations on Parabemisia myricae (Kuwana), a whitefly of Japanese origin which has been recently recorded in Italy, in severa! citrus areas of Sicily and Calabria. The results are also reported of studies on natural enemies of the new pest. Among the predators, Phytoseiid mites, a species of Hemiptera Anthocoridae and various Diptera Syrphidae have been found; preliminary notes are given on various Neuroptera Chrysopidae and Coniopterigidae and Coleoptera Coccinellidae which have been noted in the investigated area. As to the parasites, three species have been found of Hymenoptera Aphelinidae: Encarsia lutea (Masi), Encarsia meritoria Gaham and Cales noacki Howard . The second species (Encarsia meritoria) has been recorded only in Calabria, apparently not occurring in Eastern Sicily; it showed a relevant parasitic activity on Parabemisia myricae, thus a program has been started to introduce such parasitoid in Sicilian environments.
Keywords: Parabemisia myricae; Southern Italy; biology; natural enemies